Deterministic mechanisms of spiking in diffusive memristors. (August 2021) - Ushakov, Yury; Akther, Amir; Borisov, Pavel; Pattnaik, Debi; Savel'ev, Sergey; Balanov, Alexander G.
Highlights: Modeling negative differential resistance of memristors. Global bifurcations in a diffusive memristor model. Distinguishing different spiking modes of a diffusive memristor. Analyzing deterministic dynamics to understand effects of noise in a diffusive memristor. Abstract: Diffusive memristors, which have been recently fabricated and measured, attract a significant interest being among the best candidates to mimic neuron activities and to implement novel computing paradigms. Such devices are capable of exhibiting a combination of dynamical, chaotic, and stochastic phenomena needed for efficient neuromorphic computational systems. However, understanding the contribution of deterministic and stochastic dynamics to the functional properties of a diffusive memristor is still an open problem. To study the deterministic mechanisms governing the dynamics of diffusive memristors, we analyze a model of a memristive circuit when the effects of the temperature noise are neglected. We reveal instabilities, which shape the current-voltage characteristic of the device and imply the onset of current self-oscillations. Finally, the results of modeling are compared with experimentally measured current-voltage characteristics.